INVOLVEMENT OF CHILDREN IN LEGAL ISSUES FOR CRIMINAL ACTS OF TERRORISM IN INDONESIA: PHENOMENON AND INFLICTING FACTORS - Bintara Sura Priambada; Hartiwiningsih; Hari Purwadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This article discusses the involvement of children in legal issues of criminal acts of terrorism in Indonesia, including a discussion of the phenomena and factors that cause them. This research method is this research using empirical legal research (non-doctrinal). Data collection techniques in this study were carried out through interviews and literature studies. This research also uses deductive reasoning method. The results of the study show the importance of paying attention to the potential for indoctrination of radicalism to children. However, this will be difficult to prevent if the perpetrators of indoctrination are the child's own parents. The risk of indoctrination of radicalism is easier to limit and prevent if the perpetrator is another party who is not a parent. Internal factors that occur and come from within the child. In this case, it is due to the mental condition of the child who is not yet an adult as well as the intervention of the parents who were previously the parents who attracted their children to join the terrorism network. Then external factors that come from outside the child. In this case, it is generally caused by environmental factors, the development of technology and information, as well as things that are not derived from the child's internal factors. Children who are in conflict with the law in criminal acts of terrorism should still receive protection for their rights. One of them is by implementing diversion in every stage that children go through in dealing with the law in criminal acts of terrorism and optimizing deradicalization policies based on the concept of restorative justice.